Kajian Visual Kemasan Sebagai Media Informasi: (Case Study of Flying Glider Toy Product Packaging) - Ali Ramadhan; Fachmi Khadam Haeril; Rika Medina (LPPM STIKI Malang, 2019)
Packaging is one way to provide information about the products contained therein, while the information is expected to provide an obvious description. In the packaging of toys, sometimes the information provided is dominated by the image of its products. Using qualitative methods that aim to provide information based on the depictions contained in the packaging especially flying glider packaging. With the approach in the form of retrospective case series study is expected to provide answers that can help in viewing the visual packaging of toys in providing information relating to the packed product. Visual of flying glider packaging is dominated by images as information that describes the contents of the toys that packed. While the text as one way of conveying the information used as a explanation of the toy. Keywords: Visual, packaging, flying gliders, information.